What is ISO 9000 and why do I care ? - Texas Producers Group. Houston ([S.l.] : Coronet/MTI Film, 1993)
The video is a training program designed for employees at all levels who have questions about implementing one of the ISO 9000 quality standards
Keywords: Quality assurance -- Standards; ISO 9000 Series Standards